PERANCANGAN SISTEM INFORMASI RINGKASAN PULANG PASIEN DI RUMAH SAKIT MUHAMMADIYAH BANDUNG INFORMATION SYSTEM DESIGN OF PATIENT RETURN AT THE MUHAMMADIYAH HOSPITAL BANDUNG - Lasya Dwi Amelia; Yuda Syahidin; Erix Gunawan; Jeri Sukmawijaya (Media Bina Ilmiah, 2023)
This research aims to design a patient discharge summary information system using Microsoft Visual Studio 2012 at the Muhammadyah Hospital in Bandung. This research was conducted to visualize the design of the discharge summary system. A qualitative method with a descriptive approach is the research method used in this journal research. Collecting research data uses the method of observation, interviews, and literature study. The source of this research was obtained from interviews with the head of medical records and also the registration staff. The information system design used is the Prototype Method. The impact of carrying out this reporting system is to simplify and shorten the return summary. Therefore, the design of this information system is necessary so that there are no delays or incomplete discharge summaries which will prevent the doctor from making further patient visits.